PHYTOCHEMICALS AND ANTIOXIDANT ACTIVITY OF CLERODENDRUM PANICULATUM (L.) LEAF AND FLOWER EXTRACTS - DEEPA R HEBBAR; DEVIKA M; RASHMI GN; NALINI MS (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Objective: This study was designed to evaluate the phytochemicals present in the flower and leaf extracts of Clerodendrum paniculatum L., collected from Nelji village of Kodagu district . Methods: The healthy leaves and flowers of C. paniculatum were collected and the plant extracts were prepared using ethanol, hexane and distilled water separately. Phytochemical analysis was conducted using standard procedurs for the flower and leaf extracts of C. paniculatum. The antioxidant activity in leaf and flower extracts was determined by three assays, estimation of total phenolic content, reducing power assay and radical scavenging activity (DPPH) using standard procedures. Results: Phytochemical screening conducted for the flower and leaf extracts of C. paniculatum showed the presence of three phytochemicals, namely saponins, alkaloids and terpenoids. Terpenoids were commonly present in all the extracts of flower and leaf that is in both polar (aqueous and ethanol) solvent and in non-polar (hexane) solvents. The extracts tested for the antioxidant activity showed the presence of total phenolics in ethanol, aqueous and hexane extracts. The aqueous extract showed high redox potential followed by ethanol and hexane extracts. The aqueous leaf extract showed high radical scavenging activity when compared to the flower extracts of C. paniculatum. Conclusion: The present study showes C. paniculatum to be an important medicinal plant, since the flower and leaves showed good antioxidant activity. Thus it may used in the treatment of diseases and may also used in the preparation of natural or herbal drugs due to the presence of antioxidants.